Hymenophyllaceae (Polypodiopsida) na mesorregião metropolitana de Belém, Estado do Pará, Brasil - SILVA, Gisele Teixeira da (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2018)
Hymenophyllaceae (Polypodiopsida) from the Metropolitan Mesoregion of Belém, State of Pará, Brazil. In Brazil as well as in the Brazilian Amazon, most information regarding to Hymenophyllaceae is contained in floristic surveys and there are few specific studies to the family. This work presents a floristic treatment of filmy ferns from Metropolitan Mesoregion of Belem. We recorded 19 species belonging to the genera Didymoglossum (6 spp.),Hymenophyllum (3 spp.), Polyphlebium (1 sp.) and Trichomanes (9 spp.) that correspond to about 60% of filmy ferns from Pará. Trichomanes crispum and T. vittaria are new records to the studied area. The cities of Belém and Santa Barbara do Pará have greater species richness probably due to the ecological parks and to concentrate studies in these areas. Keys to the genera and species as well as descriptions, taxonomic comments, geographic distributions data, types of vegetation, substratum and illustrations are given.